The Effect of Islamic Financial Socialization and Education on Public Interest in Using Islamic Banking Services - Yati, Alan (PT. Anagata Sembagi Education, 2024)
This study used SPSS analysis tool to investigate the effect of Islamic financial socialization and education on public interest in using Islamic banking services, involving a sample of 66 respondents in two major cities in Indonesia. A survey method with a questionnaire was used to collect data, which was then statistically analyzed using SPSS. The results of data analysis showed that Islamic financial socialization and education had a significant positive impact on increasing public interest in Islamic banking services. This finding confirms that an effective educational approach in improving the understanding of Islamic finance principles, such as profit-sharing and the prohibition of riba (interest), plays an important role in supporting the growth of the Islamic banking sector in Indonesia. Consequently, Islamic banks and financial institutions need to continuously improve their Islamic financial socialization and education strategies to expand people's access to religiously-compliant financial services and to strengthen sustainable financial inclusion in the country. This study aims to explore the effect of Islamic financial socialization and education on people's interest in using Islamic banking services, using SPSS analysis tools and involving a sample of 66 respondents in two major cities in Indonesia. A questionnaire survey method was used to collect data covering respondents' perceptions and level of understanding of Islamic finance concepts. The collected data were then statistically analyzed using SPSS to evaluate the relationship between socialization and education variables with interest in using Islamic banking. The results showed that Islamic financial socialization and education had a significant impact on increasing public interest in Islamic banking services. More than 65% of respondents showed increased interest after being involved in the socialization and education program. This finding reinforces the importance of a comprehensive education strategy in explaining the principles of Islamic finance such as profit-sharing, prohibition of riba (interest), and transparency in financial practices. The implication of this study is the importance of Islamic banks and financial institutions to continue developing Islamic financial socialization and education programs as part of the effort to build public understanding and trust in Islamic financial products. This will not only support the growth of the Islamic banking sector in Indonesia, but also strengthen broader and more sustainable financial inclusion within it. As such, this study contributes to supporting sustainable economic development through the promotion and adoption of Islamic financial principles that are in line with religious values.